Numerical Study and Optimization-Based Sensitivity Analysis of a Vertical-Axis Wind Turbine - El Maani, Rabii; Radi, Bouchaib; El Hami, Abdelkhalak (Energies (Basel), 2024)
This study aims to introduce a new optimization method for designing a vertical-axis wind turbine (VAWT) that dynamically morphs its blades as a function of the tip-speed ratio (TSR) and azimuthal angle. For this purpose, the Darrieus turbine is the subject of a dynamic study under transient aerodynamic loads. By resolving the two-dimensional unsteady incompressible Navier–Stokes equation, the aerodynamic torque is obtained with the k-ϵ realizable turbulence model. A comparison between rotor operation at optimal and lower  Cp values is possible according to the investigation of flow-field characteristics for a variety of tip-speed ratio values, with experimental results so that a better understanding of the vertical-axis wind turbine’s basic physics is obtained. Then, a multi-objective optimization technique is coupled with ANSYS Workbench to increase the energy generation of VAWT blades by reducing the drag coefficient and maximizing the power coefficient. The input variables were evaluated through a sensitivity analysis, and the most important one was chosen. The analysis results of the best compromise showed that the design methodology’s output is feasible for manufacturing.